Espécies do gênero Eimeria (Apicomplexa: Eimeriidae) em Tamanduás-bandeira (Myrmecophaga tridactyla Linnaeus, 1758) em cativeiro. - Freitas, Fagner Luiz da C; Almeida, Katyane de S; Zanetti, André S; do Nascimento, Adjair A; Machado, Cé Lio R; Machado, Rosangela Z (My University, 2006)
The parasitism of the two giant anteaters adults (Myrmecophaga tridactyla), one male and one female, infected naturally with Eimeria escomeli, E. tamanduae e E. marajoensis was related in the present research. In E. escomeli oocysts were 23.9 +/- 1.89 by 19.7 +/- 1.60 microm and its sporocysts were 11.47 +/- 1.25 by 6.48 +/- 0.80 microm. In E. tamanduae oocysts were 23.52 +/- 0.95 by 20.59 +/- 0.92 microm and its sporocysts were 12.19 +/- 0.65 by 7.15 +/- 0.55 microm. In E. marajoensis oocysts were 13.5 +/- 1.7 by 13.1 +/- 1.8 microm and its sporocysts were 7.4 +/- 0.58 by 5.4 +/- 0.8 microm. Eimeria escomeli was described before parasitizing giants anteater from Bolivia, and it was point out as the first time in Brazil. The presence of E. tamanduae and E. marajoensis parasitizing giant anteaters indicate the possibility of having co-infection of them among animals of the family Myrmecophagidae.
Species of the genus Eimeria (Apicomplexa: Eimeriidae) in giant anteaters (Myrmecophaga tridactyla Linnaeus, 1758) in captivity
Keywords: animal; Edentata; Eimeria; female; male; parasitology; Animals; Female; Male; Xenarthra